Poly(butylene trisulfide)/CNT nanocomposites: synthesis and effect of CNT content on thermal properties - Milad Sheydaei; Milad Edraki (Journal of Chemistry Letters)
Polysulfide polymers are classified as high-performance materials due to their high solvent resistance and good thermal stability. In the present study, poly(butylene trisulfide) (PBTRS) was synthesized using 1,4-dichlorobutane (DCB) and sodium trisulfide (Na2S3). Then, nanocomposites are synthesized using carbon nanotube (CNT). The PBTRS characteristics were investigated by X-ray diffraction (XRD), proton nuclear magnetic resonance (1H NMR), differential scanning calorimetry (DSC), thermogravimetric analysis (TGA), and scanning electron microscopy (SEM). Also, nanocomposites were investigated by SEM, XRD, DSC, and TGA. The results showed that the melting temperature (Tm) and glass transition temperature (Tg) by increasing CNT in the matrix, occurs at higher temperatures. Moreover, with the increase of CNT in the matrix, the formation of crystals increases.